Etika dan Tax Evasion - Afriyani, Niar (E-Jurnal Akuntansi, 2023)
Tax Evasion is an action taken by taxpayers in reducing the obligation to pay taxes illegally. Cases of tax evasion are still common in Indonesia in recent years. This study aims to determine how the influence of tax justice, love of money, and religiosity on the ethical perception of tax evasion. As well as testing the role of gender moderation in the relationship between the independent variables and the dependent variable. Data collection in this study was carried out through a questionnaire. The population in this study are individual taxpayers who work in DKI Jakarta with purposive sampling technique. The data analysis technique used is multiple regression analysis. The results showed that the higher the tax justice and religiosity, the lower the ethical perception of tax evasion. The higher a person's love for money, the higher the ethical perception of tax evasion. Gender affects how high or low the influence of the independent variable on the dependent variable. Keywords: Tax Evasion; Ethical Perception; Taxation; Gender; Theory of Planned Behavior